THE RELIGIOUS CONVERSION PROCESS AS AN UNUSUAL LIFE EXPERIENCE TO THE MALAYSIAN CHINESE MUSLIM CONVERTS IN THE CONTEXT OF ADULTHOOD SELF-DIFFERENTIATION DEVELOPMENT - Loo Tuck Yee; Nadiyah Binti Elias; Mariny Abdul Ghani, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study explores the role of religious conversion as an unusual life experience in facilitating adulthood self-differentiation development in the context of Malaysia Chinese Muslim converts. It is a qualitative phenomenology study, five participants from the northern religion of Malaysia were taking part, and data were collected by semi-structured interviews. This study has identified the religious conversion has placed the Chinese Muslim converts in the hardships of (a) marginalized minority, (b) deviation and (c) association status which might facilitate self-differentiation development.